2013
DOI: 10.4103/0972-124x.118328
|View full text |Cite
|
Sign up to set email alerts
|

Acute gingival bleeding as a complication of dengue hemorrhagic fever

Abstract: Dengue fever is mosquito borne disease caused by dengue virus (DENV) of Flaviviridae family. The clinical manifestations range from fever to severe hemorrhage, shock and death. Here, we report a case of 20-year-old male patient undergoing orthodontic treatment presenting with acute gingival bleeding with a history of fever, weakness, backache, retro orbital pain and ecchymosis over his right arm. The hematological investigations revealed anemia, thrombocytopenia and positive dengue non-structural protein-1 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 11 publications
(11 reference statements)
1
17
0
Order By: Relevance
“…It has been reported that glomerular capillary dilatation, haemorrhage into the interstitium, in small and large renal vessels occur during pathogenesis of fever [38], also acute gingival bleeding has been reported in fever especially in dengue hemorrhagic fever [39]. Vasodilation of the renal vasculature and gingival bleeding as a result of hyperthermia enhanced the detection of malaria antigens in urine and saliva in this study.…”
Section: Discussionsupporting
confidence: 60%
“…It has been reported that glomerular capillary dilatation, haemorrhage into the interstitium, in small and large renal vessels occur during pathogenesis of fever [38], also acute gingival bleeding has been reported in fever especially in dengue hemorrhagic fever [39]. Vasodilation of the renal vasculature and gingival bleeding as a result of hyperthermia enhanced the detection of malaria antigens in urine and saliva in this study.…”
Section: Discussionsupporting
confidence: 60%
“…Oral manifestations of many hematological diseases are clinically similar to locally occurring lesions. [10,11] For this reason, a specific diagnosis of blood dyscrasia is difficult, if not impossible, to establish on the basis of oral findings alone. The dentist may be the first health care professional to evaluate a patient with acute gingival bleeding owing to an underlying blood dyscrasia.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical history, systemic signs of a bleeding disorder, and abnormal tests for hemostasis may help the dentist in the early detection and referral of patients for further management. [10,12,13] Causes of acute severe diffuse gingival bleeding include local and nondental causes, which include vitamin deficiencies, malignancies, such as leukemia, side effects of certain medications, and occasionally systemic diseases. Hemorrhagic disorders in which abnormal gingival bleeding is encountered include vascular abnormalities (vitamin C deficiency or allergy, e.g., Henoch-Schönlein purpura), platelet disorders [14] (e.g., thrombocytopenic purpura), hypoprothrombinemia (vitamin K deficiency), other coagulation defects (e.g., hemophilia), deficient platelet thromboplastic factor (PF3) resulting from uremia, [15] multiple myeloma, [16] leukemia, [17] and postrubella purpura.…”
Section: Discussionmentioning
confidence: 99%
“…Severe dengue infection has a tendency of developing haemorrhage involving blood hemolysis 63 , 64 and it is known that blood hemolysis contributes to the accumulation of serum ferritin as well as from damaged cells 65 . In addition, activated macrophages also secrete ferritin into plasma although its mechanism is still unknown 66 .…”
Section: Discussionmentioning
confidence: 99%